Visual inspection of cervix with acetic acid as a feasible screening test for cervical neoplasia among women attending at OPD in Rajshahi Medical College Hospital - Yusuf, Nahid; Ali, Md Ahmed; Nahar, Nazmun; Chaudhury, Shipra; Rahman, Md Zillur (KYAMC Journal, 2018)
Background: Visual inspection of cervix after application of 3-5% acetic acid (VIA) is a potential alternative to Pap smear cytology for screening of cervical cancer in resource poor settings. Objectives: This study was to evaluate the performance of visual inspection based screening approach in the detection of precancerous and early cancerous lesions of the cervix. Materials & Methods: VIA was carried out in 540 eligible women attending Gynae OPD. Detection of well-defined, opaque, acetowhite lesion close to squamocolumnar junction or in transitional zone of the cervix constituted positive VIA. All screened women evaluated by colposcopy and biopsy were taken from colposcopically suspected areas. The final diagnosis was based on histology. Results: Out of 540 patients, 328 were VIA negative and 212 were VIA positive. Colposcopy showed normal results in 340 cases, low grade CIN in 138 cases, high grade CIN in 44 cases and cancer in 18 cases. There were biopsy proven chronic cervicitis and metaplastic changes in 423 cases, CIN I in 66 cases, CIN II in 25 cases, CIN III / carcinoma-in-situ in 5 cases. The sensitivity of VIA was 74.36%, specificity 70.45%, positive predictive value 41.04%, & negative predictive value 90.85%. Conclusion: VIA can differentiate a normal cervix from a precancerous cervix with reasonable accuracy. As it is low cost and simple method, it can be set in any hospital or any health care centre of rural or urban areas of poor resource settings. KYAMC Journal Vol. 9, No.-2, July 2018, Page 56-60